MECHANISMS FOR THE DEVELOPMENT OF PRESCHOOL CHILDREN THROUGH THE MEANS OF PHYSICAL EDUCATION - Rustamov Akbar Askarovich; Ikromboyev Asadbek (Proximus Journal Publishing, 2024)
the article provides the basis for the comprehensive maturation of preschool children, their physical and mental development and strengthening their health, the results of exercise, the Healing Forces of nature, the positive impact of hygienic factors. The changes that occur in a child through natural factors aimed at giving physical loads and preventing their exhaustion, taking into account their age characteristics, are indicated when training children's body parts, teaching them to the main types of movements
Keywords: Preschool children; mechanism; physical education; physical qualities